Rights without borders? Learning from the institutional response to Iraqi refugee children in Jordan. Issue 2 (3rd March 2016) - Hart, Jason; Kvittingen, Anna
Abstract : The principle of universality is the cornerstone of the UN Convention on the Rights of the Child. The study of displaced Iraqi children in Jordan reveals the political and economic factors that can militate against universality in practice. Following an account of Iraqi displacement in Jordan and of Iraqi children's situation from a rights perspective, we consider the institutional response offered by host government, western donors, and UN agencies and International Non-Governmental Organizations. As we argue, together these different actors have created, albeit unintentionally, what may be considered a 'network of disregard' in which a relationship of mutual dependence inhibits the pursuit of a principled, non-discriminatory approach to the realisation of rights. In consequence, Iraqi refugee children are left in a state of enduring limbo: at best receiving support in a piecemeal manner. This unfortunate situation raises important issues about the child rights project as it has been conceived and operationalised.